Debates of the House of Assembly / Union of South Africa - South Africa Parliament (Cape Town, 1938)
Debates of the House of Assembly of the Union of South Africa as reported in the Cape Times. Debates of the House of Assembly / Union of South Africa. Debates of the House of Assembly / Union of South Africa = Debatten van de Volksraad / Unie van Zuid-Afrika.
108 v. 4th Session, 4th Parliament
Keywords: Sixth Session; Seventh Parliament; 11 February 1938; 16 March 1938; Vol. 31; Additional estimates (motion- Mr Havenga); wine industry; Index to Speeches; Index to Subjects; Wilkens, Mr J. (Klerksdorp); JC044692; agriculture and forestry, minister of